Water erosion in post-planting eucalyptus forests at center-east region of Minas Gerais State, Brazil - Pires, Lislane Sousa; Silva, Marx Leandro Naves; Curi, Nilton; Leite, Fernando Palha; Brito, Liziane de Figueiredo (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate soil and water losses by hydric erosion, in standard plots under natural rainfall, in different management systems of post-planting eucalyptus forests. The experiment was installed in an undulated relief, on a very clayey Typic Haplustox. The data collections were performed from October 2002 to February 2004, in rain events considered erosive. The studied systems were: native forest; planted pasture; cross slope direction eucalyptus; slop direction eucalyptus; slope direction eucalyptus with burning of crop residues, and bare soil. Among the forest systems, the cross slope direction eucalyptus is the one which is closer to the native forest in terms of soil losses, indicating the highest sustainability of the former in the water erosion context. The higher values of water losses, were found in the slope direction eucalyptus system with burning of crop residues, suggesting that the fire both increases repellence to water and diminishes water infiltration rates in soil. All the eucalyptus management systems presented soil losses below tolerance limit.
Keywords: soil and water losses; forest essences; Oxisol; management systems